2022
DOI: 10.1186/s12920-022-01412-8
|View full text |Cite
|
Sign up to set email alerts
|

Clinical value and potential mechanisms of BUB1B up-regulation in nasopharyngeal carcinoma

Abstract: Nasopharyngeal carcinoma (NPC) has insidious onset, late clinical diagnosis and high recurrence rate, which leads to poor quality of patient life. Therefore, it is necessary to further explore the pathogenesis and therapy targets of NPC. BUB1 mitotic checkpoint serine/threonine kinase B (BUB1B) was found to be up-regulated in a variety of cancers, but only two previous study showed that BUB1B was overexpressed in NPC and the sample size was small. The clinical role of BUB1B expression and its underlying mechan… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…Qin et al. also found that BUB1B is highly expressed in nasopharyngeal carcinoma and that BUB1B can promote tumor progression by regulating the cell cycle ( 34 ). Zhu et al.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Qin et al. also found that BUB1B is highly expressed in nasopharyngeal carcinoma and that BUB1B can promote tumor progression by regulating the cell cycle ( 34 ). Zhu et al.…”
Section: Resultsmentioning
confidence: 99%
“…Zeng et al found that the expression level of NDC80 in human glioblastoma cells was significantly higher than that in normal cells and that NDC80 could promote the proliferation and invasion of human glioblastoma cells (33). Qin et al also found that BUB1B is highly expressed in nasopharyngeal carcinoma and that BUB1B can promote tumor progression by regulating the cell cycle (34). Zhu et al found that BUB1 promoted the proliferation of liver cancer cells by activating the phosphorylation of SMAD2 (35).…”
Section: Results Mrna Level and Prognostic Value Of The Ska Familymentioning
confidence: 99%